Pengaruh Likuiditas, Leverage, dan Ukuran Perusahaan terhadap Penghindaran Pajak: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Malo, Mario Setiady; Harjito, Yunus; Siddiq, Faiz Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of liquidity, leverage and company size on tax avoidance. This research design is causality research which is used to prove the causal relationship of several variables. This research is quantitative research. The population in this research are mining companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sampling method used was a purposive sampling method with a total sample of 19 companies during an observation period of 5 consecutive years so that the total sample was 95. The data analysis method used was multiple linear regression analysis using SPSS version 21. The results of this research are the results of the research shows that liquidity and leverage have a significant negative effect on tax avoidance. Meanwhile, company size has no effect on tax avoidance.